A Monte Carlo Study on the Influence of TiO2 Nanoparticles on the Optical Absorbance Properties in Different Human Skin Types - Prince, Shanthi (Asian Journal of Chemistry, 2013)
Due to the decrease in the ozone layer thickness, there is more irradiation of the earth's surface with ultraviolet solar rays these days. A number of substances (sunscreens) for ultraviolet protection of human skin is being developed. Sunscreens contain organic chemical compound that absorb ultraviolet light and inorganic particulates (such as titanium dioxide-TiO2, zinc oxide or a combination of both) that reflect, scatter and absorb ultraviolet light. A five layer skin model (stratum corneum, epidermis, papillary dermis, reticular dermis and hypodermis) is proposed with top layer stratum corneum covered with sunscreen containing TiO2. Each layer is modeled with appropriate chromophores like b-carotene, bilirubin, oxyhemoglobin, deoxyhemoglobin and melanin. The monte carlo simulations are carried out for the spectral region under investigation (280-400 nm). The results obtained with and without TiO2 in the stratum corneum layer for different skin types are compared. Presence of TiO2 nanoparticles in the top layer of stratum corneum prevents significant penetration of radiation towards the underlying skin layers.